Electromyographic analysis of two different feet positions in backstroke start - de Jesus, Ka.; de Jesus, Ke.; Figueiredo, P.; Goncalves, P.; Pereira, S.; Vilas-Boas, J. P.; Fernandes, R. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to assess the electromyographic (EMG) activity of Bíceps Brachii, Tríceps Brachii, Deltoideus Anterior, Erector Spinae Longissimus, Rectus Femoris, Gluteus Maximus Gastrocnemius Medialis, muscles at two variants of the backstroke start, one performed with the feet parallel and entirely immerged (BSFI) and the other with the feet parallel and entirely emerged (BSFE). Four high level swimmers performed a 4x15 m maximal protocol of BSFI and BSFE. In both start variants the upper limbs muscles are mainly required during the initial start phases: (i) for BSFI, the Gastrocnemius Medialis showed greater electrical activity at take-off phase than hands-off and flight phases, and (ii) for BSFE, Erector Spinae Longissimus, Gluteus Maximus and Rectus Femoris registered similar electrical activity at hands-off and take-off phases.